Phenylpropanoid Metabolism in Suspension Cultures of Vanilla planifolia Andr. : III. Conversion of 4-Methoxycinnamic Acids into 4-Hydroxybenzoic Acids - Funk, Christoph (1990)
Feeding of 4-methoxycinnamic acid, 3,4-dimethoxycinnamic acid and 3,4,5-trimethoxycinnamic acid to cell suspension cultures of Vanilla planifolia resulted in the formation of 4-hydroxybenzoic acid, vanillic acid, and syringic acid, respectively. The homologous 4-methoxybenzoic acids were demethylated to the same products. It is concluded that the side chain degrading enzyme system accepts the 4-methoxylated substrates while the demethylation occurs at the benzoic acid level. The demethylating enzyme is specific for the 4-position. Feeding of [O-(14)C-methyl]-3,4-dimethoxycinnamic acid revealed that the first step in the conversion is the glycosylation of the cinnamic acid to its glucose ester. A partial purification of a UDP-glucose: trans-cinnamic acid glucosyltransferase is reported. 4-Methoxy substituted cinnamic acids are better substrates for this enzyme than 4-hydroxy substituted cinnamic acid. It is suggested that 4-methoxy substituted cinnamic acids are intermediates in the biosynthetic conversion of cinnamic acids to benzoic acids in cells of V. planifolia.